2021
DOI: 10.1111/bcpt.13648
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of cancer cell death mechanisms by curcumin: Implications to cancer therapy

Abstract: Cancer is known as a second major cause of death globally. Nowadays, several modalities have been developed for the treatment of cancer. Radiotherapy and chemotherapy are the most common modalities in most countries. However, newer modalities such as immunotherapy and targeted therapy drugs can kill cancer cells with minimal side effects. All anticancer agents work based on the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 134 publications
1
18
0
1
Order By: Relevance
“…This may be due to the concentration of cNLP used in our experiments (10 µg/mL [27 µM]). It has been previously shown that free curcumin is toxic to cancer cells ≥1 µM [ 58 ] and we have similarly demonstrated toxicity in K562 and HL-60 human leukemia cell lines treated with 15–30 µM curcumin [ 59 ]. However, since normal cells are more resistant to curcumin than cancer cells [ 47 , 48 ], presumably due to cell-cycling differences, it is therefore possible that higher curcumin concentrations (above 30 µM) may be beneficial to cell survival in quiescent cultures following IR exposures.…”
Section: Discussionsupporting
confidence: 55%
“…This may be due to the concentration of cNLP used in our experiments (10 µg/mL [27 µM]). It has been previously shown that free curcumin is toxic to cancer cells ≥1 µM [ 58 ] and we have similarly demonstrated toxicity in K562 and HL-60 human leukemia cell lines treated with 15–30 µM curcumin [ 59 ]. However, since normal cells are more resistant to curcumin than cancer cells [ 47 , 48 ], presumably due to cell-cycling differences, it is therefore possible that higher curcumin concentrations (above 30 µM) may be beneficial to cell survival in quiescent cultures following IR exposures.…”
Section: Discussionsupporting
confidence: 55%
“…Curcumin ameliorated radiation-induced pneumonitis and pulmonary fibrosis [ 112 , 113 ] and cognitive deficits (including learning and memory defects), exerted cardioprotective, neuroprotective, hepatoprotective, and renoprotective activities [ 108 , 110 ], and decreased pain severity [ 114 ]. Additionally, curcumin has antitumor effects [ 115 ] that can synergize with radiotherapy [ 116 , 117 , 118 ]; it should thus be considered a good option to increase the efficacy of radiotherapy on cancer cells, as well as to prevent the radiotherapy-induced adverse effects in normal tissues [ 112 , 114 ]. A few human studies have confirmed its efficacy for the management of radiotherapy induced dermatitis [ 119 ] and mucositis [ 120 , 121 ].…”
Section: Medical Countermeasuresmentioning
confidence: 99%
“…Curcumin and derivatives have been proposed as potential therapeutic agents in selected cancer types such as prostate, colon, breast and thyroid cancer ( Schwertheim et al, 2017 ; Mbese et al, 2019 ) and their anticancer effects have been tested in vitro and in vivo in combination with chemotherapeutic agents and radiotherapy ( Yu et al, 2021 ). Curcumin has shown to amplify the anticancer effects of drugs (e.g., doxorubicin, cisplatin, gefitinib) and radiotherapy ( Tan and Norhaizan, 2019 ; Ashrafizadeh et al, 2020 ).…”
Section: Mechanism Of Action Of Curcumin and Related Compoundsmentioning
confidence: 99%
“…Regarding curcumin capability to activate cell death, the engagement of various pathways has been recently reported ( Yu et al, 2021 ). Besides, in the literature it is widely reported that normal cells are less sensitive to curcumin treatment than cancer cells and curcumin does not induce any apoptotic death in normal cells and tissues ( Syng-Ai et al, 2004 ).…”
Section: Mechanism Of Action Of Curcumin and Related Compoundsmentioning
confidence: 99%